Algorithms, contexts, governance: An introduction to the special issue. (April 2022) - Gritsenko, Daria; Markham, Annette; Pötzsch, Holger; Wijermars, Mariëlle
This introduction to the special issue on algorithmic governance in context offers an outline of the field and summarizes each contribution to the issue.